Assessment of death registration coverage and its delays in district Faridkot: an urban rural comparison - ., Anupamdeep; Padda, Preeti; Gupta, Sanjay; Gupta, Vishal; Devgan, Shalini; Monga, Shamim (International Journal Of Community Medicine And Public Health, 2019)
Background: Death registration has been made compulsory under the RBD Act 1969 as it acts as a back bone for planning services and formulates policies. According to CRS 2013, at national level, 70.9% of deaths were registered which is far from magic figure of 100% despite of concerted efforts of government. So this study was conducted to assess the coverage of death registration and its delays. Methods: A cross sectional study was conducted over a period of one year where 332 households(166 each from urban and rural area reporting deaths in last two years were included in study after taking informed written consent. Relevant information was collected using a predesigned and pretested questionnaire by house to house survey. Coverage was calculated with possession of death certificate. Data was compiled and analyzed using EpiInfo07 (CDC, Atlanta, USA). Results: Out of 332 deaths, 245 (74%) out of which only140 (57%) possessed the death certificate. The main cause of death was cardiac diseases. Maximum coverage was seen in the age group 41-60 years. Delay in registration was seen in 48% with significantly higher proportion in rural area (59%) than in urban area (40%). Reasons for delay were time constraints, lack of knowledge and financial constraints. Socio demographic variables like religion, caste, type of family, family size and SES were not found to be associated with delay. Conclusions: The coverage of death registration was comparatively higher than national data and delay was observed in about half of the death registration coverage.